Pathological complete response in MMR-deficient/MSI-high and KRAS-mutant patient with locally advanced rectal cancer after neoadjuvant chemoradiation with immunotherapy: A case report - Zhang, Mai; Yang, Hua; Chen, Ling; Du, Kunli; Zhao, Lina; Wei, Lichun (Frontiers in Oncology, 2022)
To date, preoperative chemoradiation (CRT) is the standard of care for patients with locally advanced rectal cancer (LARC) regardless of status of mismatch repair. Immunotherapy showed promising results in the neoadjuvant treatment trials in patients with mismatch repair-deficient (dMMR) or high microsatellite instability (MSI-H) LARC. The efficacy of CRT plus programmed death 1 (PD-1) inhibitor in these patients with complex gene mutation remains unclear. Additionally, very few studies reported on whether such combination could induce abscopal effect. We report a case of dMMR and MSI-H LARC with KRAS mutation that achieved pathological complete response of primary lesion and liver metastases after neoadjuvant short-course radiotherapy followed by four cycles chemotherapy of XELOX plus PD-1 inhibitor tislelizumab and a subsequent total mesorectal excision. This case indicates that this combined treatment strategy has remarkable clinical response both in locoregional and distant diseases, which potentially leads to reduction in the risk of distant metastases and better locoregional control for this subgroup of population.